2012
DOI: 10.1186/1471-2474-13-29
|View full text |Cite
|
Sign up to set email alerts
|

The cost effectiveness of NHS physiotherapy support for occupational health (OH) services

Abstract: Background: Musculoskeletal pain is detrimental to quality of life (QOL) and disruptive to activities of daily living. It also places a major economic burden on healthcare systems and wider society. In 2006, the Welsh Assembly Government (WAG) established a three tiered self-referral Occupational Health Physiotherapy Pilot Project (OHPPP) comprising: 1.) telephone advice and triage, 2.) face-to-face physiotherapy assessment and treatment if required, and 3.) workplace assessment and a return-to-work facilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 28 publications
0
49
0
1
Order By: Relevance
“…Regarding the influence of pain on work, we emphasize the importance of the physiotherapist’s role. According to Phillips et al 19 ) , a physiotherapeutic program for improving the physical health status of patients with pain significantly helps reduce work-related problems and costs. Thus, any physiotherapeutic approach first requires a complete patient history that identifies labor activities and activities of daily living to establish effective interventions that promote physical autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of pain on work, we emphasize the importance of the physiotherapist’s role. According to Phillips et al 19 ) , a physiotherapeutic program for improving the physical health status of patients with pain significantly helps reduce work-related problems and costs. Thus, any physiotherapeutic approach first requires a complete patient history that identifies labor activities and activities of daily living to establish effective interventions that promote physical autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Measure for reduced productivity at work/ while working 31 (39, 41-44, 56, 60-65, 69, 70, 72, 77, 82, 87, 89, 94, 95, 98, 103, 104, 114, 115, 118, 119, 123, 124, 128) Source presenteeism Employee survey 18 (41, 44,56,62,64,69,72,82,87,89,94,95,98,104,115,118,119, 123) Simulated / assumptions 7 (39, 43, 44,103,114,124, 128) Previous studies 6 (42,60,61,63,65,70) Firm data 1 (115) Employer survey 1 (77) Survey/instrument presenteeism 56,62,69,82,94,95,118,119,123) Days (unspecified) 49 (39, 40, 42, 46,49,(51)(52)(53)(54)58,60,62,64,66,71,72,74,75,(77)(78)…”
Section: Presenteeismmentioning
confidence: 99%
“…Phillips et al evaluated the cost-e®ectiveness of physiotherapy support for NHS occupational health services and found that physiotherapists were not only skilled to deal with a range of musculoskeletal disorders of the back, neck and upper and lower limbs, but this service had a cost bene¯t which represents value for money. 11 Occupational health doctors and nurses also reported challenges that physiotherapists may experience when providing occupational health rehabilitation. Participants viewed the occupational health department as a complex working environment that is in°uenced not only by clinical care, but by demanding occupational health challenges and organizational changes.…”
Section: Discussionmentioning
confidence: 99%